Jump squat is more related to sprinting and jumping abilities than Olympic push press - Loturco, I.; Kobal, R.; Maldonado, T.; Piazzi, A. F.; Bottino, A.; Kitamura, K.; Abad, C. C. C.; Pereira, L. A.; Nakamura, F. Y. (International Journal of Sports Medicine, 2017)
The aim of this study was to test the relationships between jump squat (JS) and Olympic push press (OPP) power outputs and performance in sprint, squat jump (SJ), countermovement jump (CMJ) and change of direction (COD) speed tests in elite soccer players. 27 athletes performed a maximum power load test to determine their bar mean propulsive power (MPP) and bar mean propulsive velocity (MPV) in the JS and OPP exercises. Magnitude-based inference was used to compare the exercises. The MPV was almost certainly higher in the OPP than in the JS. The MPP relative to body mass (MPP REL) was possibly higher in the OPP. Only the JS MPP REL presented very large correlations with linear speed (r>0.7, for speed in 5, 10, 20 and 30?m) and vertical jumping abilities (r>0.8, for SJ and CMJ), and moderate correlation with COD speed (r=0.45). Although significant (except for COD), the associations between OPP outcomes and field-based measurements (speed, SJ and CMJ) were all moderate, ranging from 0.40 to 0.48. In a group composed of elite soccer players, the JS exercise is more associated with jumping and sprinting abilities than the OPP. Longitudinal studies are needed to confirm if these strong relationships imply superior training effects in favor of the JS exercise.